ANALISIS PENERAPAN GREEN MANUFACTURING DALAMPEMBUATAN BOARDING BRIDGE DI PT X - Daffa Alandro (2021)
Boarding Bridge is a passenger bridge that is used to cross from the airport terminal to the aircraft door, or vice versa, in the process of making Boarding Bridge, it cannot be separated from the application of Green Manufacturing in order to maintain the creation of a factory environment that can minimize pollution and environmental damage due to industrial activities. The research that will be conducted aims to obtain an analysis of Green Manufacturing on the work environment air, noise, and emission from vehicle, from the Boarding Bridge factory. The research company is PT X, a multinational company engaged in construction and manufacturing. The research begins by making a Key Performance Indicators related to the environmental conditions of Boarding Bridge factory then the results obtained are analyzed and the Key Performance Indicator is calculated. The results of the analysis show that Green Manufacturing is well executed and the Key Performance Indicator has reached 80%.